1987
DOI: 10.1128/mcb.7.12.4472
|View full text |Cite
|
Sign up to set email alerts
|

T-cell proliferation involving the CD28 pathway is associated with cyclosporine-resistant interleukin 2 gene expression.

Abstract: CD28 is a homodimeric glycoprotein expressed on the surface of a major subset of human T cells that has recently been identified as a member of the immunoglobulin supergene family. The binding of monoclonal antibodies to the CD28 antigen on purified T cells does not result in proliferation; however, previous studies have shown that the combination of CD28 stimulation and protein kinase C activation by phorbol myristate acetate (PMA) results in T-cell proliferation that is independent of both accessory cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
278
1
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 465 publications
(300 citation statements)
references
References 34 publications
19
278
1
2
Order By: Relevance
“…A recent report has suggested that Vav-1 has no apparent role in co-stimulation based on the evidence that Vav-1-deficient T cells activated by anti-CD28 Ab and PMA showed no defect in proliferation and IL-2 production (55). This type of stimulation which generates CsA-resistant lymphokine expression (56), is likely to be supraphysiological and to bypass relevant signaling steps elicited by cell surface receptors (57). Indeed, CD28 enhancement of a TCR-induced increase in IL-2 mRNA is potently, though not entirely, inhibited by CsA (56, 58) and we found that NF-AT activation induced by Vav-1 overexpression/CD28 engagement (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…A recent report has suggested that Vav-1 has no apparent role in co-stimulation based on the evidence that Vav-1-deficient T cells activated by anti-CD28 Ab and PMA showed no defect in proliferation and IL-2 production (55). This type of stimulation which generates CsA-resistant lymphokine expression (56), is likely to be supraphysiological and to bypass relevant signaling steps elicited by cell surface receptors (57). Indeed, CD28 enhancement of a TCR-induced increase in IL-2 mRNA is potently, though not entirely, inhibited by CsA (56, 58) and we found that NF-AT activation induced by Vav-1 overexpression/CD28 engagement (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…The number of known costimulatory molecules has increased drastically since the characterization of CD28 as a costimulator of T cells nearly 20 years ago (7). Many TNFR family members such as CD30 (8,9), OX40 (10), and 4-1BB (11,12) have also been shown to be involved in T cell costimulation.…”
mentioning
confidence: 99%
“…Costimulation signals delivered through CD28 has been reported to confer resistance to the immunosuppressant cyclosporin A [26]. The A17 and M2 T cell clones used in these experiments do not express CD28 and resting VIEC and AIEC do not express B7.…”
Section: Costimulation Is Sensitive To Cyclosporin a But Not Ctla4igmentioning
confidence: 89%
“…HUVEC [28], but not AIEC or VIEC (Fig. 8), confer upon costimulated T cells partial resistance to the immunosuppressant cyclosporin A. Cyclosporin A resistance is also observed after costimulation through CD28 [26], which activates the principle factor for IL-2 transcription, NFAT, through a separate pathway [41] involving phosphorylation of the jun subunit of AP-1 [42]. However, costimulation by AIEC, VIEC, or HUVEC does not involve the B7-CD28 pathway because these EC do not express B7 and costimulation is not inhibited by soluble CTLA4 (CTLA4Ig), which blocks signaling through B7 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation